PENGARUH DISIPLIN KERJA GURU DAN PENGELOLAAN PROSES BELAJAR MENGAJAR TERHADAP MOTIVASI BELAJAR SISWA KELAS XII JURUSAN IPS DI SMAN 15 PADANG - Daniati, Nia; Ansofino, Ansofino; Dahen, Lovelly Dwinda (Pendidikan Ekonomi, 2014)
ABSTRACTThis research was conducted in SMA l5 Padang on the effect of teacher labor discipline and management of teaching and learning process to students motivation X11 majoring in social studies class at SMAN 15 Padang . The purpose of this study is ( 1 ) To determine whether the effect of the work discipline of teachers to students motivation X11 majoring in social studies class at SMAN 15 Padang . ( 2 ) To determine whether the effect of the management of the learning process of the students motivation X11 majoring in social studies class at SMAN 15 Padang . ( 3 ) To determine whether the effect of the teacher labor discipline and management of the learning process of the students motivation X11 majoring in social studies class at SMAN 15 Padan.This research is a descriptive study associative , population in this study were all students majoring in social studies in grades X11 SMAN 15 Padang . 144 people . The samples are 60 people with the proportional random sampling method . Primary data and secondary data that has been collected is then analyzed statistically by descriptive and inductive analysis through multiple regression analysis using SPSS version 16.0The results of the analysis of the data obtained that ( 1) There is a significant influence teacher labor discipline and management of the learning process of the students motivation X11 majoring in social studies class at SMAN 15 Padang sig of 0.000 , which is smaller than Î± = 0.05 . ( 2 ) There is a significant influence teacher labor discipline on the students motivation X11 majoring in social studies classes in SMA 15 Champaign sig 0.003 < 0.05 0.266 level influences . ( 3 ) there is a significant influence on the management of the learning process students motivation X11 majoring in social studies classes in SMA 15 Champaign sig 0.000 < 0.05 0.295 level influences.Based on the above results it can be concluded that the teacher labor discipline and management of teaching and learning are two factors that can influence on students motivation X11 majoring in social studies class at SMAN 15 Padang . It is thus suggested to teachers to better improve labor discipline and implementing the learning process even better so as to increase students motivation X11 majoring in social studies class at SMAN 15 Padang.